Conceptualising the Work of the Indigenous Screen Producer as a Creative System of Practice - Milligan, Christina Charlotte (Auckland University of Technology, 2022)
This thesis presents a detailed analysis of the work of the producer in the screen industry, centring on the producer in the Indigenous screen production ecology of Aotearoa New Zealand. The theoretical underpinning of this study is Mihaly Csikszentmihalyi’s systems model of creativity, which frames creative practice as the product of three interconnected features: the ‘individual’ who creates new work, the existing body of knowledge or ‘domain’ within which they practise, and the network of experts or ‘field’ who recognise the value of the new work. This approach provides a framework for analysing the work of the producer, locating it within its surrounding social and cultural contexts. Drawing on interviews, archival research, autoethnography and a case study, the thesis presents a detailed history of the emergence of Māori filmmaking from the beginning of the 20th Century to the present day. It then focuses on the practice of a specific group of feature film producers to establish how their own personal histories, philosophies and experiences have shaped the work they do. Finally, it develops a case study of a feature documentary to reveal, through the author’s personal experience, the producer’s decision-making process and how that is shaped by both internal and external creative and industrial forces. The thesis as a whole follows a media production studies approach and, through this, offers a comprehensive understanding – historical, social, creative, industrial – of how Māori filmmaking has developed and the importance of the individual producer within this development. In doing so, the thesis offers an Indigenous revision of Mihaly Csikszentmihalyi’s systems model of creativity, connecting the elements of the individual, the domain and the field through the holistic framework of te ao Māori, the Māori worldview.